COMPARATIVE ANALYSIS OF THREE LEAF EXTRACTS OF IXORA COCCINEA LINN. FOR THEIR PROTECTIVE AND ANTI- OXIDANT POTENTIALS AND CORRELATION WITH ANALYTICAL DATA - POORNIMA SHYAM; P.K.SURESH (International Journal of Pharma and Bio Sciences, 2013)
The vast potential of plants as a source of drugs against various diseases has been harnessed from times immemorial. Plants synthesize primary and secondary metabolites which protect the cells from Reactive oxygen species ROS. Many of the degenerative disorders and aging are caused by ROS. The extraction was carried out using the direct extraction method using ethanol, water and ethanol + water (80:20) as solvents. In this paper we have worked on Ixora coccinea Linn. leaves which have been used for their many medicinal properties in the traditional healing practices. The green chemistry approach to reduce volatile solvents and toxicity from solvent usage has also been tested. Comparative evaluation of the extracts in terms of their anti- oxidant potentials (DPPH method, Lipid - per oxidation, FRAP, Total-phenolic content and total anti-oxidant capacity, DNA and RBC protection potentials, Phytochemical analysis, and also HPLC and GC-MS analysis. The results showed the method to be efficient in terms of yield, bioactivity and also the analytical analysis wherein the ethanol + water extract showed better potentials as compared to the parent solvents(ethanol and water).This approach helps reduce the usage of volatile solvents, the toxicity induced by solvents and the amount of solvents used Further studies with different ratios are underway in view of the encouraging results from this study.